ESTIMASI TEMPERATUR CONDENSOR REFLUX (136 H09) PADA REGENERATION UNIT UNTUK PENGHEMATAN KONSUMSI TEG - Tessa Audia Linarta; Christyfani Sindhuwati; Hardjono Hardjono (Politeknik Negeri Malang, 2021)
The dehydration process is one of the processes that is often found in natural gas processing plants. TEG (triethylene glycol) is a glycol compound commonly used in natural gas dehydration processes. TEG is used as an absorbent for water absorption which is still contained in natural gas which can cause hydrate and corrosion. This absorption process is carried out at the TEG contactor, the TEG that has been used will be regenerated, if it has been regenerated, the TEG will be used again. The purpose of this research is to estimate the appropriate temperature for the TEG regeneration unit absorption process, because there are many TEG losses in this process. TEG losses occur in the TEG regenerator and are usually caused by the temperature of the reflux condenser which is not quite right, causing the TEG to be evaporated out into the atmosphere with water vapor. Losing the TEG is a problem for critical operations in dehydrated systems. The step used to reduce TEG losses is to heat the temperature of the condenser to 100°C by changing the reboiler temperature from 190°C to 197.3°C.